Serum Cystatin C in Patients with Delayed Graft Function - Boncheva M. (Sciendo, 2016)
Despite recent studies showing that serum Cystatin C (CysC) is a better marker for glomerular filtration rate (GFR) than the ubiquitously used creatinine, the clinical utility of these findings remains to be evaluated. This marker is very sensitive for allograft function after renal transplantation. The concentration of CysC was compared with that of the creatinine. Decreased renal function was followed in 64 transplanted patients. Serum CysC significantly correlated with creatinine in healthy controls (r = 0.625, p < 0.0001), whereas in the transplanted patients the mean serum creatinine and CysC concentrations were: 81 ± 13 mmol/L and 0.90 ± 0.22 mg/L, respectively. Serum CysC and creatinine significantly correlated throughout the post transplantation period (r = 0.686, p < 0.001), but we confirmed differences between kinetics of these parameters. In the first four days after transplantation the CysC concentration was normalized faster than the creatinine concentration. Development of acute rejection episode (between 5 and 7 days) showed high sensitivity and specificity of the changes of CysC compared with those of creatinine.